2009
DOI: 10.1111/j.1740-0929.2009.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of young cross‐bred calves immediately after long‐haul road transportation and after one week of habituation

Abstract: We investigated 10 suckling cross-bred calves (Japanese Black (Wagyu) x Holstein) and collected data on the physiological stress responses of the young calves to long-haul road transportation. All calves were male and 21-47 days of age. The calves were obtained at a livestock market and were transported from the market to the university in a commercial livestock vehicle. The total haul distance and time were 306.9 km and 7 h, respectively. The calves were deprived of food and water during transportation. Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
2
14
1
Order By: Relevance
“…This study supported the findings of Jacobson and Gook (1998) and Van de Water et al (2003) who reported an increased HR at loading and unloading, which could result from psychological stress caused by the different environment and being handled (Uetake et al, 2009). In addition, the greater HR at loading than unloading was probably due to better procedures at the destination farm (e.g., reduced degree of inclination of the loading ramp) compared with the handhng conditions at the transit center.…”
Section: Hematological Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…This study supported the findings of Jacobson and Gook (1998) and Van de Water et al (2003) who reported an increased HR at loading and unloading, which could result from psychological stress caused by the different environment and being handled (Uetake et al, 2009). In addition, the greater HR at loading than unloading was probably due to better procedures at the destination farm (e.g., reduced degree of inclination of the loading ramp) compared with the handhng conditions at the transit center.…”
Section: Hematological Variablessupporting
confidence: 89%
“…In summer, the return to the initial value of lactate was slower, indicating that the adaptation of calves after transportation could be more time consuming in the hot season. According to Todd et al (2000) and Uetake et al (2009), an increased lactate value was observed after a long-distance transport. This finding suggests that the calves had a minimal degradation of muscle glycogen and a minor degree of fear, which normally results in the liberation of catecholamines, with rapid glycogenolysis and gluconeogenesis (Chacon et al, 2005).…”
Section: Hematological Variablesmentioning
confidence: 90%
“…Repeated handling also resulted in a decrease in cortisol response (Andrade et al 2001;Solano et al 2004) and repeated exposure to noise during handling resulted in decreased heart rate and level of movement (Waynert et al 1999). A study by Uetake et al (2009) also found that rectal temperature, measured following road transport, was reduced (although not significantly) after 1 week of habituation to transport. This core temperature response is a reflection of increased heat production, possibly through activation of the sympathetic nervous system (Sjaastad et al 2003).…”
Section: Discussionmentioning
confidence: 85%
“…The biochemical changes due to transportation stress include concentrations of glucose, NEFA (Non-esterifies free fatty acid), muscle enzymes, such as CK etc. (Ishiwata et al, 2008;Uetake et al, 2009;Uetake et al, 2011). Measurements reflective of dehydration have also been reported, including increased packed cell volume (Sporer et al, 2007) and serum protein (Ishiwata et al, 2008;Sporer et al, 2008).…”
mentioning
confidence: 97%